Current treatment of cervical cancer: progress and prospects - Pérez Villena, Joan Flaubert (2024)
Standard treatment for early cervical cancer is mainly by laparotomy. Lymph nodeassessment is essential, utilizing sentinel lymph nodes and pelvic lymphadenectomy.If intraoperative lymph node involvement is identified, it is preferable to avoiddissection and opt for chemoradiotherapy. Radical type C hysterectomy is the usualapproach, although extrafascial hysterectomy may be considered in low-risk patients. The SHAPE study suggests that there are no significant differences in recurrence-free survival between the two types of hysterectomy. In young women who wish to preserve their fertility, conization or radical trachelectomy are viable options instages IA2-IB1. In stages IB3 and IIA2, concurrent chemoradiotherapy is preferredand has shown more favorable survival results. Neoadjuvant chemotherapy isapplied in settings where radiotherapy is not available. For patients with earlydisease, radiotherapy may be an alternative if there are contraindications to surgery.Finally, adjuvant radiotherapy is recommended for patients with high-risk factorsafter surgery, while low-risk patients do not require additional treatment, thusallowing for a personalized approach based on individual patient characteristics.